Copyright and mass digitization - Borghi, Maurizio; Karapapa, Stavroula (Oxford : Oxford University Press, 2013)
In an age of mass digitization, does copyright law need to change, and if so, how? This thought-provoking book considers whether the purposes, activities and effects of mass digitization are consistent with copyright law and principles arguing for a comprehensive regulatory framework for the use of works in mass digital libraries and archives.
Description based on online resource; title from home page (viewed on Apr. 24, 2013).
Includes bibliographical references and index.
Keywords: Copyright; Digital media -- Law and legislation